2011
DOI: 10.4088/jcp.10m06011yel
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Loxapine for Inhalation in the Treatment of Agitation in Patients With Schizophrenia

Abstract: ClinicalTrials.gov identifier: NCT00369577.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 0 publications
3
59
0
2
Order By: Relevance
“…127 Efficacy results through 24 hours from two randomized, placebo-controlled phase 3 studies of 5 mg and 10 mg Staccato® loxapine revealed that agitation (as measured by the excitatory component of the Positive and Negative Syndrome Scale 128 ) in agitated patients with schizophrenia was significantly reduced versus placebo treatment (p р 0.0001) at 10-20 minutes following administration of the 10-mg dose of Staccato® loxapine. 129,130 A similar rapid response was observed in agitated patients with bipolar disorder who received the same dose. 127 The most common side effects (> 10%) were altered taste, dizziness, and sedation, with no serious treatmentrelated adverse events reported.…”
Section: Unmet Needs In Pharmacological Rapid Tranquilizationsupporting
confidence: 73%
“…127 Efficacy results through 24 hours from two randomized, placebo-controlled phase 3 studies of 5 mg and 10 mg Staccato® loxapine revealed that agitation (as measured by the excitatory component of the Positive and Negative Syndrome Scale 128 ) in agitated patients with schizophrenia was significantly reduced versus placebo treatment (p р 0.0001) at 10-20 minutes following administration of the 10-mg dose of Staccato® loxapine. 129,130 A similar rapid response was observed in agitated patients with bipolar disorder who received the same dose. 127 The most common side effects (> 10%) were altered taste, dizziness, and sedation, with no serious treatmentrelated adverse events reported.…”
Section: Unmet Needs In Pharmacological Rapid Tranquilizationsupporting
confidence: 73%
“…Oral dosage is between 50 and 200 mg/day. Plasma half-life is approximately 4 h, with a terminal half-life of up to 19 h. For inhaled loxapine, the dose has been found to be effective at 5 or 10 mg per administration and studies allowed up to three doses/24 h [26]. Loxapine is metabolized in the liver and largely excreted through the kidneys.…”
Section: Clinical Pharmacologymentioning
confidence: 98%
“…Efficacy was demonstrated in two pivotal trials in patients with schizophrenia [26,27] and in one trial in patients with bipolar disorder, manic or mixed episode. [28] Effect sizes for the reduction of agitation were comparable with those for intramuscular options.…”
Section: Antipsychoticsmentioning
confidence: 99%